2022
DOI: 10.1038/s41598-022-21137-z
|View full text |Cite
|
Sign up to set email alerts
|

Spatial–temporal trends of COVID-19 infection and mortality in Sudan

Abstract: Since its emergence, the coronavirus disease 2019 (COVID-19), is constantly affecting many parts of the globe and threatening millions of lives worldwide. Charting and aligning disease incidence to identify spatial clustering and patterns continue to be a substantial pathway to understanding disease epidemiology and is essential for implementing effective planning and prevention strategies. A national descriptive study was implemented to present the infection and mortality rates of the COVID-19 pandemic in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…This nding is consistent with ndings from a study in Namibia that showed that more urban areas had earlier exposure to SARS-CoV-2 and increased transmission rates during waves [6]. Paradoxically, less dense SEAs had a higher prevalence in this study, a nding in contrast to ndings from a study in Nairobi and another study in Sudan [4,5]. This nding could be explained by wealthier urban residential areas with a high prevalence of cases, which are also lower in population density than poorer urban residential areas (e.g., compounds) in Zambia.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This nding is consistent with ndings from a study in Namibia that showed that more urban areas had earlier exposure to SARS-CoV-2 and increased transmission rates during waves [6]. Paradoxically, less dense SEAs had a higher prevalence in this study, a nding in contrast to ndings from a study in Nairobi and another study in Sudan [4,5]. This nding could be explained by wealthier urban residential areas with a high prevalence of cases, which are also lower in population density than poorer urban residential areas (e.g., compounds) in Zambia.…”
Section: Discussionsupporting
confidence: 90%
“…The incidence of SARS-CoV-2 in Africa has been shown to vary by geographic location, with evidence of spatial spread from high-incidence countries to low-incidence neighbouring countries [3]. Increasing population density has been associated with increasing SARS-CoV-2 prevalence in Kenya and Sudan [4,5]. In Namibia, the COVID-19 pandemic began in urban regions and progressively spread to more rural regions.…”
mentioning
confidence: 99%
See 1 more Smart Citation